2019
DOI: 10.1136/bjsports-2018-099547
|View full text |Cite
|
Sign up to set email alerts
|

Injury epidemiology and risk factors in competitive artistic gymnasts: a systematic review

Abstract: BackgroundArtistic gymnastics is reported to have some of the highest injury rates in sports, which limits participation and often involves considerable medical expenses.PurposeTo critically appraise the epidemiological literature on injury patterns and risk factors in competitive artistic gymnastics.Study designSystematic review.MethodsSix databases were searched for articles that investigated injuries in competitive artistic gymnasts. Injury incidence, prevalence and risk factor data were extracted, alongsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 60 publications
5
67
1
1
Order By: Relevance
“…[14][15][16][17] Coaches also described other acute injuries that their gymnasts experienced, which have been previously reported to occur in gymnastics. [43][44][45] These included shoulder injuries in MAG gymnasts, lower limb injuries in TRA gymnasts and hamstring strains in WAG gymnasts.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Coaches also described other acute injuries that their gymnasts experienced, which have been previously reported to occur in gymnastics. [43][44][45] These included shoulder injuries in MAG gymnasts, lower limb injuries in TRA gymnasts and hamstring strains in WAG gymnasts.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are partially in line with those of the two review studies on injury type and frequency in gymnastics [22,23]; the authors found that most injuries affected the lower and upper extremities, followed by the back, shoulders and neck. Another recent review of 10 studies that investigated the location of injuries in female gymnasts reported the lower limbs were the most commonly injured area of the body [24]. However, older results in 64 Australian elite-level and sub-elite-level female gymnasts showed that the low back was the second most commonly reported area of injury, immediately after the ankle and foot [49].…”
Section: Injury Statusmentioning
confidence: 99%
“…Importantly, measures for preventing sport-related injuries should also be included in overall physical preparedness and training/dietary strategies. Of note, the incidence and severity of injuries is relatively high among artistic gymnasts, especially advanced-level female gymnasts [22][23][24]. A recent systematic review of 12 studies including 843 female gymnasts that evaluated injury type and frequency showed that most injuries affected the lower extremities, followed by the upper extremities, the torso/spine and neck [23].…”
Section: Introductionmentioning
confidence: 99%
“…To further increase its suitability for estimating risk of bias for the specific objective of this systematic review, the original checklist was modified. Such modifications have been done before in previous systematic reviews [41][42][43]. The answer option "Not applicable" was added to several questions, as for some study designs particular questions were not applicable, resulting in a different total score depending on the study design.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%